Kuat Tekan Paving Block Geopolimer Abu Sawit (Palm Oil Fuel Ash) Dengan Perawatan Suhu Ruang - Syarif, Harriad Akbar; Olivia, Monita; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Geopolymer is an environmentally friendly alternative construction material made from the process of activating the base material rich in silicon (Si) and aluminum (Al) with a solutionof alkaline activators. In this study, using the ashes of oil derived from Dumai, Riau Province as the base material of geopolymer. With the eco-friendly construction material that theproduct is made with reference to a standard paving blocks. This study is based on variations of modulus activator, dosage activators, and the addition of cement type 1 (OrdinaryPortland Cement) for the treatment of room temperature (setting time) on the composition of the mixture. This study aims to determine the amount of use of the base material (palm oil fuelash) from the comparison alkaline activator with palm oil fuel ash used in paving block geopolymer based treatment time and its influence on the physical properties of the geopolymer paving block. The results showed that the strong increase in modulus of paving blocks are influenced by activators in combination with the addition of cement to each composition.Keywords: palm oil fuel ash, geopolymer, paving block, modulus activator, dosage activator